Psychological Impact Analysis on Adolescents with Cyberchondria: a Literature Review - Henny Indreswari; Shabrina Muyassirotul 'Aliyah; Achmad Miftachul 'Ilmi; Khairul Bariyyah (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2022)
The development of information and communication technology has led teenagers to use gadgets and the internet for prolonged periods of time. Besides being used as a means of entertainment and communication, teenagers nowadays tend to search for health information through the internet. However, some people are anxious about their health condition and begin to diagnose themselves or seek certainty on the internet. Excessive searching for health information on the internet can lead to cyberchondria, which is associated with fear and anxiety. To support these efforts, this study aims to analyze the psychological impact of cyberchondria on teenagers. The methodology employed in this study was a literature review that involved five stages: gathering literature, selecting relevant materials, evaluating the literature, drawing conclusions, and discussing the research results, using a total of 12 relevant articles. The results showed that the psychological impact of cyberchondria on teenagers consisted of cognitive, affective, and conative effects. Moreover, cyberchondria can also cause non-specific somatic complaints in teenagers. The findings of this study can serve as a reference for future researchers interested in the topic of cyberchondria